Modelling IT brand values supplied by consultancy service companies: empirical evidence for differences - Alcaide, Ángeles; Guadalajara, Natividad; De La Poza, Elena (Technological and Economic Development of Economy, 2021)
Brands are the most precious intangible companies’ assets. Company managers need to know their brand value and the aspects determining it. As no transparent brands market exists, the main objective of this study was to model brand values that the world’s main valuation consultants publish. The obtained results indicate that 80% of the value of these brands is accounted for by both the net results of the companies that own brands and their value on the Stock Exchange. These results allow brand values to be estimated using quantitative and objective information by simple methods, unlike those used by valuation consultants. Moreover, one temporal analysis and another for different industries confer these outcomes consistency. First published online 18 December 2020